(3QSGdI egQGQjS GdMcje CQSdgG dHYV ef GdJdGePIs - (3egQGQjS GdMcjes
(3ChdgG (B:s
(3CQSd egQGQS GdMcje GdajdSha Edi HYV GdJdGePI GdeLJgOjf GdPjf bO bGQHhG OQLI GdadGSaI LfHc Gddg eSGhF GdCNdGb s
(3BNQgG (B:s
(3GdJi gi CUhd GdYGde GdeGA hGdfgGQ hGdghi hGdCQV hgPg gi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B6s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs